Can Transparency of Information Reduce Embezzlement? Experimental Evidence from Tanzania - Salvatore Di Falco; Brice Magdalou; David Masclet; Marie Claire Villeval; Marc Willinger (Institute for the Study of Labor (IZA), 2016)
Embezzlement is a major concern in various settings. By means of a sequential modified dictator game, we investigate theoretically and experimentally whether making information more transparent and reducing the number of intermediaries in transfer chains can reduce embezzlement and improve the recipients' welfare. Consistent with reference-dependent preferences in terms of moral ideal, we show that the impact of transparency is conditional on the length of the transfer chain and on the position of the intermediaries in the chain. Its direct effect on image encourages honesty. Its indirect effect via expectations plays in the opposite direction, motivating individuals to embezzle more when they expect that the following intermediary will embezzle less. Senders react positively to a reduction of the length of the chain but negatively to transparency.
Keywords: C91; D83; 330; embezzlement; corruption; dishonesty; transparency; experiment